Spin induced exchange bias and lattice modulation in Nd1−xEuxCrO3. (1st February 2021) - Gupta, Pragya; Pal, D
Abstract: We report the evolution of coupled phonons and exchange bias ( EB ) in perovskite-type Nd1− x Eu x CrO3 ( x = 0.0, 0.05, and 0.10) samples by means of temperature-dependent Raman spectroscopy and dc magnetization measurements. We observed a non-monotonic behavior of the EB field around the temperature T *, which lies between the antiferromagnetic ordering temperature ( T N ) and spin-reorientation transition temperature ( T SR ). The temperature dependence of phonon modes related to antistretching and bending of CrO6 octahedra and Nd 3+ /Eu 3+ ion vibration below T N confirms the strong spin–phonon coupling. The T * found from the non-monotonicity of the EB is imprinted with the additional anomaly observed in the low-temperature spin–phonon behavior. The phonon modes and phonon anomaly are also verified using the density functional theory-based calculations.